Effect of topical antimicrobial therapy and household cleaning on meticillin‐resistant Staphylococcus pseudintermedius carriage in dogs. (27th September 2021) - Frosini, Siân‐Marie; Bond, Ross; King, Ruth; Feudi, Claudia; Schwarz, Stefan; Loeffler, Anette
Abstract: Background : Meticillin‐resistant Staphylococcus pseudintermedius (MRSP) is a multidrug‐resistant canine pathogen with a low zoonotic potential. This study investigated MRSP carriage and clearance through topical antimicrobial therapy and household cleaning in dogs recovered from MRSP infection. Methods : Dogs were swabbed for MRSP carriage; household contamination was assessed using contact plates. Carrier dogs were allocated randomly to receive topical fusidic acid and chlorhexidine/miconazole treatment combined with owners implementing a household hygiene protocol (H&T) or implementation of hygiene alone (H) over three weeks. Carriage‐negative dogs were monitored monthly. The relatedness of isolates over time was investigated by pulsed‐field gel electrophoresis (PFGE). Results : At inclusion, MRSP carriage was confirmed in 31/46 (67.4%) index dogs and 16/24 (66.7%) contact dogs, and contamination was found in 18/40 (45%) environments. In dogs completing all cycles, interventions cleared carriage in 5/9 (55.6%) dogs in group H&T and 2/6 (33.3%) in group H. Environmental contamination was infrequent but associated with carrier dogs ( p = 0.047). Monthly monitoring of initially negative dogs showed intermittent carriage in 9/14 dogs. PFGE‐concordance was found among all 34 MRSP isolated from eight index dogs over time. Conclusion : MRSP carriage was common in dogs after recovery from infection. Topical antimicrobial therapy temporarily eliminated carriage but recurrence was frequent. Management efforts must include the prevention of recurrent infections and hygiene.